A method for constructing [epsilon]-value functions for the Bolza problem of optimal control - Pustelnik, Jan (Zielona Góra: Uniwersytet Zielonogórski)
The problem considered is that of approximate minimisation of the Bolza problem of optimal control.
Keywords: non-linear optimisation; Bolza problem; optimal control; Hamilton-Jacobi equation; dynamic programming